Bioinspired Anti‐Fogging and Anti‐Fouling Artificial Compound Eyes (Advanced Optical Materials 17/2022). Issue 17 (5th September 2022) - Li, Minjing; Yang, Tongzhen; Yang, Qing; Fang, Zheng; Bian, Hao; Zhang, Chengjun; Hou, Xun; Chen, Feng
Abstract : A bioinspired artificial compound eye (ACE) is fabricated by femtosecond laser wet etching, soft lithography, and polydimethylsiloxane (PDMS) swelling methods. The resultant ACE sample is close‐packed with more than 3000 high‐quality microlenses on a spherical macrolens over its large viewing angle. The trapped silicone oil in the PDMS endows the device with excellent water repellence and anti‐fogging ability besides its high optical performance. Such remarkable characteristics make the minimized component competitive in vision systems under humid environment conditions. For further details see article number 2200861 by Qing Yang, Feng Chen and co‐workers.